Improving MRP Precision in Engineering and Manufacturing Sectors: Meningkatkan Ketepatan MRP di Sektor Teknik dan Manufaktur - Ardana, Muhammad Rizky; Putra, Boy Isma (Universitas Muhammadiyah Sidoarjo, 2024)
This study evaluates the effectiveness of Material Requirement Planning (MRP) in the engineering and manufacturing sector through a five-month empirical investigation focused on production processes. Utilizing a combination of literature review, interviews, and direct observation, the research aimed to compare theoretical MRP calculations with actual raw material usage. Results highlighted significant discrepancies between projected and actual figures, indicating potential inaccuracies in current MRP applications. These findings underscore the need for refining MRP systems to enhance forecasting precision and inventory management, suggesting that integrating real-time data and improving algorithmic methodologies could bridge the existing gap between theory and practice in industrial manufacturing. Highlights: Essential Raw Material Management: Key for timely production and meeting customer needs. MRP Efficiency: PT. Weiss Tech uses MRP for precise raw material calculations. Accuracy Assessment: Research evaluates MRP accuracy through literature, interviews, and observation. Keywords: Raw Materials, MRP, Inventory Control